2021
DOI: 10.1101/2021.02.08.21251186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global impact and cost-effectiveness of one-dose versus two-dose human papillomavirus vaccination schedules: a comparative modelling analysis

Abstract: Background: To eliminate cervical cancer as a public health problem, WHO currently recommends routine vaccination of adolescent girls with two doses of the human papillomavirus (HPV) vaccine before sexual debut. However, many countries have yet to implement this because of financial or logistical barriers to delivering two doses outside the infant immunisation programme. Methods: Using three independent HPV transmission models, we estimated the long-term health benefits and cost-effectiveness of one-dose vers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A preprint modelling study has shown that a single dose of HPV vaccine even with somewhat lower efficacy, but with higher coverage can have greater population-level effect than two doses. 30 Herd immunity created in the population through high coverage could potentially compensate for any waning protection of a vaccine over time at an individual level. 15 A judicious recommendation to introduce a single dose of HPV vaccine and ensure high coverage of HPV vaccination will contribute to elimination of cervical cancer in a more affordable manner.…”
Section: Discussionmentioning
confidence: 99%
“…A preprint modelling study has shown that a single dose of HPV vaccine even with somewhat lower efficacy, but with higher coverage can have greater population-level effect than two doses. 30 Herd immunity created in the population through high coverage could potentially compensate for any waning protection of a vaccine over time at an individual level. 15 A judicious recommendation to introduce a single dose of HPV vaccine and ensure high coverage of HPV vaccination will contribute to elimination of cervical cancer in a more affordable manner.…”
Section: Discussionmentioning
confidence: 99%
“…44 Sixty-four million cervical cancer deaths are projected to be avoided in the next 98 years by reducing the recommended regimen from 2-to 1dose based on dynamic modeling. 45 The introduction of generic HPV vaccines could immediately disrupt the global market, providing access to affordable vaccines for national programs.…”
Section: Costs Affordabilitymentioning
confidence: 99%